Lens opacity as a predictor of retinal vasculature change following cataract surgery - Mackenbrock, Lars; Xu, An Ting L.; Łabuz, Grzegorz; Augustin, Victor A.; Yildirim, Timur Mert; Auffarth, Gerd U.; Khoramnia, Ramin (Scientific reports, 2025)
Cataract surgery, one of the most common surgical procedures worldwide, significantly improves visual acuity and quality of life for patients. However, recent studies suggest that it may have broader implications for ocular health, including changes in retinal perfusion. This prospective clinical study investigates the relationship between preoperative lens opacity and postoperative changes in macular perfusion using optical coherence tomography in 46 patients. Objective metrics were assessed automatically using a custom computer script. The analysis revealed significant increases in vessel density, diameter, and complexity across the superficial, intermediate, and deep retinal vascular plexuses, with the most pronounced changes occurring within the first postoperative week. A strong correlation was observed between preoperative nuclear lens opacity and the increase in macular perfusion, suggesting that reduced light transmission through dense cataracts may drive postoperative functional hyperemia. In contrast, surgical parameters such as phacoemulsification energy showed no significant association, and intraocular pressure reduction correlated only with subtle vascular perimeter changes. These findings indicate that enhanced light exposure following cataract removal—rather than just inflammation or mechanical factors—likely stimulates adaptive retinal metabolic responses. Clinically, this highlights the importance of preoperative lens opacity assessment as a predictor of vascular remodeling, potentially informing strategies to mitigate complications in the short and long term.